Transcriptome reveals the dysfunction of pancreatic islets after wound healing in severely burned mice. Issue 5 (20th November 2022) - Liu, Xinzhu; Xie, Xiaoye; Li, Dawei; Liu, Zhaoxing; Niu, Yuezeng; Shen, Bowen; Zhang, Bohan; Song, Yaoyao; Ma, Jinglong; Zhang, Ming; Shi, Zhiyuan; Shen, Chuan'an
Abstract : There are glucose metabolism disorders in mice at the eighth week after severe burns, which are caused by low islet cell proliferation, downregulation of protein processing, and less ATP production. Abstract : BACKGROUND: Severely burned patients have a higher risk of diabetes mellitus after healing, but its mechanism remains unclear. Therefore, the purpose of the study was to explore the influence of burns on pancreatic islets of mice after wound healing. METHODS: Forty-two male C57BL/6 mice were randomized into a sham group and a burn group and subjected to sham treatment or a third-degree burn model of 30% total body surface area. Fasting blood glucose was detected weekly for 8 weeks after severe burns. Glucose-stimulated insulin secretion was measured 8 weeks post severe burns. Islets of the two groups were isolated and mRNA libraries were sequenced by the Illumina sequencing platform. The expressions of differentially expressed genes (DEGs) related to the cell cycle and the amounts of mitochondrial DNA were detected by quantitative real-time polymerase chain reaction after gene ontology, gene set enrichment analysis, and protein-protein network analysis. Hematoxylin-eosin staining of pancreatic tail tissue and adenosine triphosphate (ATP) assay of islets were performed. RESULTS: The levels of fasting blood glucose were significantly higher within 8 weeks post severe burns. Glucose-stimulated insulin secretion was impaired at the eighth week post severe burns. Totally 128 DEGs were selected. Gene ontology and gene set enrichment analysis indicated that the pathways related to the cell cycle, protein processing, and oxidative phosphorylation were downregulated. The expressions of DEGs related to the cell cycle showed a consistent trend with mRNA sequencing data, and most of them were downregulated post severe burns. The cell mass of the burn group was less than that of the sham group. Also, the concentration of ATP and the amount of mitochondrial DNA were lower in the burn group. CONCLUSION: In the model of severe-burned mice, disorders in glucose metabolism persist for 8 weeks after burns, which may be related to low islet cell proliferation, downregulation of protein processing, and less ATP production. Abstract :